The effect of emotion regulation on happiness and resilience of university students: The chain mediating role of learning motivation and target positioning - Chen, Xiaoxue; Huang, Zejuan; Lin, Wei (Frontiers in Psychology, 2022)
To investigate the effect and mechanism among emotion regulation, relationship, happiness, learning motivation, target positioning, and resilience of university students with left-behind experience. A total of 904 university students in China were included in this cross-sectional survey from April to May this year. The self-administered questionnaires, including the adapted Mental Health Scale with a Healthy Personality Orientation for College Students, were used to construct structural equations to test the chain mediating effects of learning motivation and target positioning based on a multi-stage whole-group sample of university students. Emotion regulation indirectly affected happiness and resilience through the chain mediating effect of learning motivation and target positioning. Emotion regulation indirectly affected happiness through the mediating effect of interpersonal relationship. Learning motivation and target positioning play the chain mediating role in the effect of emotion regulation on happiness and resilience.